Evaluation of the Bending Strength, Impact Strength, and Morphological Properties of Wheat Straw Fiber/Paper Mill Sludge/Polypropylene Composites - Habibollah Khademieslam; Mehdi Kalagar (BioResources, 2016)
Composite production of polypropylene polymers was considered in this work as the matrix, filled with the fiber of wheat straw and paper mill sludge; different ratios were evaluated relative to their potential as reinforcement materials. Maleic anhydride polypropylene (MAAP) was used at 3% by weight. The bending modulus of elasticity of the composites significantly increased with both types of filler. The highest bending modulus of the composites was found with 40% of paper mill sludge. Using 40% wheat straw fiber decreased bending strength, but the addition of paper mill sludge increased bending strength. The highest bending strength of the composites related to polypropylene/10% of wheat straw fiber and 30% of paper mill sludge. In terms of impact strength, the use of paper mill sludge had a higher impact on strength than wheat straw fiber composites. The inclusion of MAPP improved the mechanical properties of all composites. Scanning electron micrographs showed that the composite paper mill sludge improved the adhesion and dispersion of the filler (paper mill sludge/fiber paper instead of wheat) in the matrix.